TPE (thermoplastic elastomer) composite material as well as preparation method and application thereof
By adding polyurethane and polyester elastomers of specific hardness to SEBS, combining compatibility and antistatic agents, the problems of poor antistatic ability and insufficient peeling force of TPE materials are solved, and the high antistatic properties of TPE composite materials are achieved and peel force, suitable for ABS adhesive application.
Patent Information
- Application Number
- CN202411536391.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-14
AI Technical Summary
The TPE material of SEBS as the main material has poor anti-static ability and insufficient peeling force when it is a sealing ABS, which limits its application in high-demand scenarios.
By adding polyurethane elastomer and polyester elastomer of specific hardness to SEBS, and combining compatibilizers and antistatic agents, the polarity, processability and hardness of the material are regulated, and the antistatic properties and peeling power of the TPE composite material are improved.
It realizes good antistatic properties and high peeling force of TPE composite materials, and is suitable for the adhesive-encapsulation applications of ABS materials, enhancing the functionality and safety of the product.
Smart Images

Figure BDA0005111654880000021 
Figure BDA0005111654880000081 
Figure BDA0005111654880000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer material modification, and more specifically, to a TPE composite material and a preparation method and application thereof. Background Art
[0002] Acrylonitrile Butadiene Styrene (ABS) is a widely used thermoplastic engineering plastic. It is composed of three monomers: acrylonitrile (A), butadiene (B) and styrene (S). The relative content of these three monomers can be changed arbitrarily to make resins with various properties. ABS material has excellent comprehensive properties. First, acrylonitrile provides high hardness and strength, heat resistance and chemical corrosion resistance; butadiene gives ABS material high elasticity and toughness, making it not easy to break when impacted; styrene improves the processing and molding characteristics of ABS material and improves its antistatic properties. These characteristics make ABS material widely used in many fields, such as automotive parts, home appliances, toys, medical equipment, etc.
[0003] Thermoplastic Elastomer (TPE) is a high-performance material with rubber properties and plastic processing performance. It has the properties of cured rubber at room temperature and can be plasticized and deformed at high temperatures. It has excellent processing functions, does not require vulcanization, can be recycled, and reduces costs. TPE materials can be processed through molding processes such as injection molding, extrusion, and blow molding. TPE materials are widely used in various industries and daily life fields due to their excellent physical and chemical properties; among them, injection molding and bonding TPE materials to ABS materials can achieve the combination of the two materials and utilize their respective advantages.
[0004] SEBS (styrene-ethylene / butylene-styrene block copolymer) is a type of thermoplastic elastomer with excellent aging resistance, heat resistance, compression deformation resistance and good mechanical properties. Therefore, by injection molding and bonding it to ABS materials, the surface of the product can be made soft and the functionality and added value of the product can be increased. For example, a Chinese patent entitled "TPE material for encapsulating ABS and its preparation process" uses SEBS as the main material to obtain a TPE material with a high success rate for encapsulating ABS.
[0005] However, SEBS has poor antistatic ability and is prone to static electricity. Static electricity adsorbs dust and other substances, which not only affects the appearance of the product, but may also cause static electricity discharge, thereby causing sparks or other safety issues. In addition, although the prior art has proposed TPE materials with a high success rate for ABS material encapsulation, it pays less attention to the issue of peeling force. It may still have insufficient peeling force, which may limit the application of ABS encapsulated TPE materials in certain high-requirement scenarios, such as sports equipment, medical devices, etc.
[0006] Therefore, it is necessary to solve the problem that the TPE material with SEBS as the main material has poor antistatic ability and insufficient peeling force when used as the encapsulation material of ABS. Summary of the invention
[0007] The primary purpose of the present invention is to overcome the problems of the existing ABS-coated TPE material with ethylene elastomer as the main material, such as poor antistatic ability, insufficient peeling force and the need to maintain good resistance to compression deformation, and to provide a TPE composite material.
[0008] A further object of the present invention is to provide a method for preparing the above TPE composite material.
[0009] A further object of the present invention is to provide the use of the above TPE composite material in preparing the encapsulation of ABS material.
[0010] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0011] A TPE composite material comprises the following components in parts by weight:
[0012]
[0013] The Shore hardness of the polyester elastomer is 27D-42D; the Shore hardness of the polyurethane elastomer is 69A-85A.
[0014] The inventors of the present invention have found that adding a certain amount of polyurethane elastomer with a specific hardness to SEBS elastomer can increase the polarity of the material and improve the peeling force of the TPE composite material on the ABS material. However, if the polyurethane elastomer is further added, the peeling force cannot be further improved, and the good compression set resistance of the SEBS elastomer itself will also deteriorate. The reason may be that the processing performance of the polyurethane elastomer is not good, resulting in poor uniformity of the components of the TPE composite material, thereby deteriorating the peeling force. Adding a compatibilizer has some improvement, but it is still not obvious.
[0015] The inventors of the present invention further discovered that by adding a certain amount of polyester elastomer with a certain hardness in addition to a certain amount of polyurethane elastomer with a certain hardness, the release force of the TPE composite material can be improved to a good level because the polyester elastomer can improve the polarity of the material and give the material good processing properties.
[0016] Too much polyester elastomer cannot be added, because its hardness is relatively high. Adding too much will deteriorate the peeling force of the material when it is used as a coating. Similarly, if the hardness of the polyester elastomer is too high, it will not be conducive to improving the peeling force of the TPE composite material.
[0017] That is, by controlling the hardness and dosage of both the polyurethane elastomer and the polyester elastomer and coordinating with the compatibilizer, the polarity, processability and hardness of the TPE composite material can be balanced, so that the peeling force of the TPE composite material can reach a good level.
[0018] The invention adds antistatic agent to improve the antistatic property of TPE composite material. The inventors of the invention also found that the addition of polyester elastomer is conducive to further improving the antistatic property of TPE composite material, which may be related to the good processability given to the material by polyester elastomer.
[0019] In addition, the inventors of the present invention have found that due to the regulation of the hardness of both the polyester elastomer and the polyurethane elastomer and the improvement of the compatibility with other components, the compression deformation resistance of the TPE composite material is also maintained.
[0020] In the present invention, the amount of SEBS elastomer can be 25, 27, 29, 31, 33 or 35 parts by weight. The amount of softening oil can be 15, 17, 19, 21, 23, 25, 27, 29, 31, 33 or 35 parts by weight; the amount of polyester elastomer can be 15, 17, 19, 21, 23 or 25 parts by weight; the amount of polyurethane elastomer can be 10, 12, 14, 16, 18 or 20 parts by weight; the amount of antistatic agent can be 5, 7, 9, 11, 13 or 15 parts by weight; the amount of compatibilizer can be 3, 5, 7, 9 or 10 parts by weight; the amount of filler can be 0, 2, 4, 6, 8, 10, 12, 14, 16, 18 or 20 parts by weight.
[0021] In the present invention, SEBS elastomer is used as the main resin, and its content accounts for at least 18wt% of the TPE composite material.
[0022] Preferably, the styrene content of the SEBS elastomer is 25-35wt%. The styrene content of the SEBS elastomer can be measured according to GB / T 13646-2013.
[0023] Preferably, the viscosity of the SEBS elastomer measured at 25° C., toluene as a solvent, and a SEBS elastomer concentration of 10 wt % is 400 to 3000 cp.
[0024] In the present invention, the viscosity of the SEBS elastomer can be measured according to Q / SH1085 130-2006.
[0025] More preferably, the viscosity of the SEBS elastomer measured at 25° C., toluene as solvent, and SEBS elastomer concentration of 10 wt % is 400-2000 cp. Within this range, the TPE composite material has better antistatic properties and higher peeling force.
[0026] More preferably, the viscosity of the SEBS elastomer measured at 25° C., toluene as solvent, and SEBS elastomer concentration of 10 wt % is 2000-3000 cp. Within this range, the TPE composite material has better anti-compression deformation capability.
[0027] In the present invention, SEBS elastomer refers to styrene-ethylene-butylene-styrene block copolymer.
[0028] Preferably, the SEBS elastomer is a linear structure SEBS elastomer.
[0029] Preferably, the kinematic viscosity of the softening oil is 90 to 120 mm 2 / s. The kinematic viscosity of softened oil can be measured according to ASTM D455-2015.
[0030] Preferably, the open flash point of the softening oil is ≥250° C. The open flash point of the softening oil can be measured according to ISO2592-2017.
[0031] Preferably, the softening oil is at least one of paraffin oil or naphthenic oil, more preferably paraffin oil.
[0032] In the present invention, the Shore hardness of the polyester elastomer may specifically be 27, 28, 30, 32, 35, 38 or 40D.
[0033] Preferably, the Shore hardness of the polyester elastomer is 28 to 35 D. Within this range, the TPE composite material has higher compression deformation resistance and peeling force.
[0034] Preferably, the polyester elastomer is at least one of a polyether polyester elastomer or a polyester polyester elastomer.
[0035] More preferably, the soft segment of the polyether polyester elastomer is at least one of polytetramethylene glycol (PTMG), polyethylene glycol (PEG) or polybutylene glycol (PBG).
[0036] More preferably, the soft segment of the polyester-based polyester elastomer is at least one of polyglycolide, polylactide or polycaprolactone.
[0037] In the present invention, the Shore hardness of the polyester elastomer can be measured according to ISO 7619-2010.
[0038] In the present invention, the Shore hardness of the polyurethane elastic material can be 69, 70, 72, 75, 78, 80, 72, 84 or 85A.
[0039] Preferably, the Shore hardness of the polyester elastomer is 70-80 A. Within this range, the peeling force of the TPE composite material is higher.
[0040] Preferably, the polyurethane elastomer is at least one of a polyether polyurethane elastomer or a polyester polyurethane elastomer.
[0041] More preferably, the soft segment of the polyether polyurethane elastomer is at least one of polytetramethylene glycol (PTMG), polyethylene glycol (PEG) or polybutylene glycol (PBG).
[0042] More preferably, the soft segment of the polyester polyurethane elastomer is at least one of polyglycolide, polylactide or polycaprolactone.
[0043] In the present invention, the Shore hardness of the polyurethane elasticity can be measured according to ISO 7619-2010.
[0044] Preferably, the antistatic agent is a polyether olefin antistatic agent, which is at least one of a polyether amide antistatic agent, an alkyl sulfonate antistatic agent, a polyether olefin antistatic agent or conductive carbon black.
[0045] More preferably, the antistatic agent is a polyetheramide antistatic agent. The antistatic agent has better compatibility in the component system of the present invention and better antistatic performance of the TPE composite material.
[0046] Preferably, the compatibilizer is a maleic anhydride grafted compatibilizer.
[0047] More preferably, the maleic anhydride grafted compatibilizer is at least one of SEBS grafted maleic anhydride, PP grafted maleic anhydride or POE grafted maleic anhydride.
[0048] More preferably, the maleic anhydride grafting rate in the maleic anhydride grafted compatibilizer is 1.0-4.0 wt %. The maleic anhydride grafting rate can be obtained by chemical titration method (KOH-ethanol solution) test.
[0049] Preferably, the filler is at least one of calcium carbonate, talc or kaolin.
[0050] Preferably, the average particle size of the filler is 800-1200 mesh. Fillers with a certain average particle size can be obtained by sieving.
[0051] Preferably, the TPE composite material further comprises 0.1 to 2 parts of other additives.
[0052] Optionally, the other auxiliary agent is at least one of an antioxidant, a light stabilizer or a lubricant.
[0053] Optionally, the antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant 1790, antioxidant 168 or antioxidant DLTP.
[0054] Optionally, the light stabilizer is at least one of a hindered amine light stabilizer or a triazine light stabilizer.
[0055] Optionally, the hindered amine light stabilizer is at least one of light stabilizer 622, light stabilizer 944, light stabilizer 3853 or light stabilizer 123; the triazine light stabilizer is at least one of UV-234, UV-236 or UV-237.
[0056] Optionally, the lubricant is at least one of erucamide, oleamide or silica.
[0057] The preparation method of the TPE composite material comprises the following steps: firstly mixing the SEBS elastomer and softening oil, then mixing with the remaining components, melt-extruding, and granulating to obtain the TPE composite material.
[0058] Preferably, the temperature of the melt extrusion is 170-210°C.
[0059] Preferably, the melt extrusion is carried out in an extruder, the screw aspect ratio of the extruder is (48-56):1, and the screw speed is 250-400 r / min.
[0060] The application of the above TPE composite material in preparing the encapsulation material of ABS material is also within the protection scope of the present invention.
[0061] A rubber-coated component comprises a coated component and a rubber-coated layer, wherein the coated component is made of ABS material, and the rubber-coated layer is made of the above-mentioned TPE composite material.
[0062] The ABS material refers to a material using ABS resin as a main resin.
[0063] Compared with the prior art, the present invention has the following beneficial effects:
[0064] The TPE composite material of the present invention not only has good antistatic performance and anti-compression deformation ability, but also has high peeling force on ABS material, so it can be widely used in the encapsulation material of ABS material. DETAILED DESCRIPTION
[0065] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0066] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:
[0067] SEBS elastomer 1#: Brand: Globaprene7551, manufacturer: Li Changrong, 10% content toluene viscosity
[0068] 2000CP;
[0069] SEBS elastomer 2#: brand name is Globaprene7554, manufacturer is Li Changrong, 10% content toluene viscosity 400CP;
[0070] SEBS elastomer 3#: Brand name is Globaprene7533, manufacturer is Li Changrong, viscosity of 5% toluene content is 400CP, viscosity of 10% toluene content is >2500CP.
[0071] Softening oil 1#: paraffin oil, brand Catenex T 141K, manufacturer Shell, kinematic viscosity 95mm 2 / s, open flash point 270℃;
[0072] Softening oil 2#: paraffin oil, brand name PLAXENE 6110, manufacturer Total, kinematic viscosity 120mm 2 / s, open flash point 280℃;
[0073] Polyester elastomer 1#: H28DMG, manufacturer Jiangyin Hechuang, hardness 28D;
[0074] Polyester elastomer 2#: H35DMG, manufacturer Jiangyin Hechuang, hardness 35D;
[0075] Polyester elastomer 3#: H40DMG, manufacturer Jiangyin Hechuang, hardness 40D;
[0076] Polyester elastomer 4#: KH-A170, manufacturer: Keheng Polymer (Guangdong), hardness 20D;
[0077] Polyester elastomer 5#: H45DMG, manufacturer Jiangyin Hechuang, hardness 45D;
[0078] Polyurethane elastomer 1#: M80, manufacturer: Meirui New Materials, hardness 80A;
[0079] Polyurethane elastomer 2#: M70, manufacturer: Meirui New Materials, hardness 70A;
[0080] Polyurethane elastomer 3#: M85, manufacturer: Meirui New Materials, hardness 85A;
[0081] Polyurethane elastomer 4#: E80, manufacturer: Meirui New Materials, hardness 82A;
[0082] Polyurethane elastomer 5#: E260, manufacturer: Meirui New Materials, hardness 60A;
[0083] Polyurethane elastomer 6#: M90, manufacturer: Meirui New Materials, hardness 90A;
[0084] Compatibilizer: SEBS-g-MAH, SEBS FG 1901, Kraton Polymers;
[0085] Antistatic agent 1#: polyether olefin antistatic agent, PELESTAT-230, manufacturer Sanyo Chemical,
[0086] Antistatic agent 2#: polyether olefin antistatic agent, PELESTAT-201, manufacturer Sanyo Chemical;
[0087] Antistatic agent 3#: polyetheramide antistatic agent, PELESTAT-6500, manufacturer: Sanyo Chemical;
[0088] Filler: Heavy calcium carbonate, MLT-818, manufacturer: Meilitai;
[0089] Other additives 1#: obtained by mixing antioxidant 1076 and antioxidant 168 at a mass ratio of 1:2, and both antioxidant 1076 and antioxidant 168 are commercially available;
[0090] Other additives 2#: obtained by mixing light stabilizer 944 and light stabilizer UV-234 at a mass ratio of 3:2, both of which are commercially available;
[0091] Unless otherwise specified, the components (eg filler, other auxiliary agent 1# and other auxiliary agent 2#) selected in each parallel example and comparative example are the same commercially available products.
[0092] The performance of the TPE composite materials provided in the embodiments and comparative examples of the present invention was measured according to the following test methods:
[0093] (1) Glue peeling strength: The test method is in accordance with VDI 2019. The specific process is: first, ABS is made into a 2.0 mm thick 150*40 mm rectangular plate through an injection molding process, and then the rectangular plate is placed in a glue mold. The TPE composite material is bonded to the surface of the ABS (brand KF-730, manufacturer Liaoning Jinfa) plate through an injection molding process. The injection molding temperature is 240°C. Use a universal testing machine and a special fixture to peel the TPE composite material from the glue test plate. Measure and record the force during the peeling process. The larger the value, the greater the glue peeling strength, that is, the better the glue bonding.
[0094] (2) Surface resistivity: The surface resistivity of the material is tested according to standard ISO 14309-2019.
[0095] (3) Compression set: The compression set performance of the material was tested according to standard ISO 815-2-2008.
[0096] The TPE composite materials provided in the embodiments and comparative examples of the present invention are prepared as follows:
[0097] 1) Weigh each component according to the formula, first mix the SEBS elastomer and softening oil evenly to obtain a premix, and let it stand for more than 24 hours.
[0098] 2) mixing the premix and other components, and then feeding them into a twin-screw extruder from a main feed, and subjecting them to melt extrusion and granulation, a TPE composite material is obtained; wherein the screw aspect ratio of the twin-screw extruder is 52:1; the screw speed is 300 r / min, and the temperatures in each melt temperature zone are 170° C., 180° C., 190° C., 195° C., 195° C., 195° C., 195° C., 195° C., 195° C., and 200° C.
[0099] Examples 1 to 13
[0100] Examples 1 to 13 provide a series of TPE composite materials, whose formulas are shown in Table 1.
[0101] Table 1 Formulas of Examples 1 to 13 (parts by weight)
[0102]
[0103]
[0104] Comparative Examples 1 to 9
[0105] Comparative Examples 1 to 9 provide a series of TPE composite materials, whose formulas are shown in Table 2.
[0106] Table 2
[0107]
[0108] The properties of the TPE composite materials of the embodiments and comparative examples were measured according to the above-mentioned test methods. The test results are shown in Table 3.
[0109] Table 3 Performance results of TPE composite materials of various embodiments and comparative examples
[0110]
[0111]
[0112] From Table 3, we can see that:
[0113] The surface resistivity of the TPE composite materials of Examples 1 to 13 is all 8.0*10 10 The compression permanent deformation is all below 55%, and the peeling force of ABS encapsulation is all above 6.3N / mm, indicating that the TPE composite material of the present invention not only has good antistatic performance and anti-compression deformation ability, but also has high peeling force to ABS material.
[0114] In Comparative Example 1, too much polyester elastomer is added, and the TPE composite material has poor resistance to compression deformation and low peeling force on ABS material. In Comparative Example 2, the hardness of the polyester elastomer added is too low, and the TPE composite material has poor resistance to compression deformation. In Comparative Example 3, the hardness of the polyester elastomer added is too high, and the TPE composite material has poor resistance to compression deformation and low peeling force on ABS material. In Comparative Example 4, no polyester elastomer is added, and the TPE composite material has low peeling force on ABS material, and the antistatic performance is reduced relative to Example 1. In Comparative Example 5, too much polyurethane elastomer is added, and the resistance to compression deformation is poor, and the TPE composite material has low peeling force on ABS material. In Comparative Example 6, the hardness of the polyurethane elastic added is too low, and the resistance to compression deformation is poor. In Comparative Example 7, the hardness of the polyurethane elastic added is too high, and the peeling force on ABS material is low. In Comparative Example 8, no polyurethane elastomer is added, and the TPE composite material has low peeling force on ABS material. In Comparative Example 9, no compatibilizer is added, and the resistance to compression deformation is poor, and the TPE composite material has low peeling force on ABS material.
[0115] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A TPE composite material, characterized in that: The composition comprises the following components in parts by weight: The Shore hardness of the polyester elastomer is 27D-40D; the Shore hardness of the polyurethane elastomer is 69A-85A.
2. The TPE composite material according to claim 1, characterized in that: The viscosity of the SEBS elastomer measured at 25° C., toluene as a solvent, and a SEBS elastomer concentration of 10 wt % is 400-3000 cp.
3. The TPE composite material according to claim 1, characterized in that: The kinematic viscosity of the softening oil is 90 to 120 mm 2 / s.
4. The TPE composite material according to claim 1, characterized in that: The polyester elastomer is at least one of a polyether polyester elastomer and a polyester polyester elastomer.
5. The TPE composite material according to claim 1, characterized in that: The polyurethane elastomer is at least one of a polyether polyurethane elastomer and a polyester polyurethane elastomer.
6. The TPE composite material according to claim 1, characterized in that: The antistatic agent is a polyether olefin antistatic agent, which is at least one of a polyether amide antistatic agent, an alkyl sulfonate antistatic agent, a polyether olefin antistatic agent or conductive carbon black.
7. The TPE composite material according to claim 1, characterized in that: The compatibilizer is a maleic anhydride grafted compatibilizer.
8. The method for preparing the TPE composite material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: firstly mixing SEBS elastomer and softening oil, then mixing with remaining components, melt-extruding, and granulating to obtain the TPE composite material.
9. Use of the TPE composite material according to any one of claims 1 to 7 in preparing an encapsulating material for ABS material.
10. A rubber-coated part, comprising a coated part and a rubber-coated layer, characterized in that: The material of the coated component is ABS material, and the material of the rubber coating layer is the TPE composite material according to any one of claims 1 to 7.